answersLogoWhite

0

Add like terms to like:

(2z - 20) + (3z + 5) = (2z + 3z) + (-20 + 5)

= 5z - 15

2z is shorthand for z+z, 3z is shorthand for z+z+z, so:

2z + 3z = (z+z) + (z+z+z)

= z+z+z+z+z

= 5z

Or, to put it another way, just add the coefficients:

2z + 3z = (2+3)z

= 5z.

User Avatar

Wiki User

14y ago

Still curious? Ask our experts.

Chat with our AI personalities

MaxineMaxine
I respect you enough to keep it real.
Chat with Maxine
LaoLao
The path is yours to walk; I am only here to hold up a mirror.
Chat with Lao
EzraEzra
Faith is not about having all the answers, but learning to ask the right questions.
Chat with Ezra

Add your answer:

Earn +20 pts
Q: How can you find the sum of 2z-20 and 3z plus 5?
Write your answer...
Submit
Still have questions?
magnify glass
imp